THE BURDEN OF QUARANTINE ON MENTAL HEALTH AMIDST COVID-19 PANDEMIC: A CROSS SECTIONAL STUDY - Khan, Taimoor Ashraf; Qureshi, Muhammad Mahad; Zahid, Muhammad Abdullah; Hussain, Ejaz; Ashraf, Muhammad; Channa, Ali Akbar (Pakistan Armed Forces Medical Journal, 2020)
Objective: To gauge the frequency of post traumatic stress disorder, stress, anxiety and depression amongst the general population that has been quarantined in public quarantines. Study Design: Cross sectional study. Place and Duration of Study: Two months duration Mar to May 2020 at rural development authority building (Quarantine facility), Quetta. Methodology: Total 377 individuals participated in the survey. Pre-validated ‘Depression Anxiety Stress Scale’ and ‘The Impact of Event Scale-Revised’questionnaire were used to interview the individuals. Results: The age ranged between 18 and 53 with a mean age of 30.9 years ± 4.9. Out of 377 participants 17 (4.5%) were seen to match a score on ‘The Impact of Event Scale-Revised’ that was positive for Post Traumatic Stress Disorder. On ‘Depression Anxiety Stress Scale’ scoring 25 (6.68%) showed symptoms indicative of depression, 19 (5%) for anxiety and 5 (1.3%) for stress. Conclusion: Quarantine has significant psychological impact which includes Post-traumatic Stress Disorder, depression, anxiety and stress on the quarantined individuals in mass public quarantines.